FUNDAMENTALS OF NAQSHBANDIYA TEACHING IN ENGLISH SOURCES - Azimovna, Abulova Zilola; Abdulloevna, Ahmedova Aziza (International Journal of Psychosocial Rehabilitation, 2020)
The rich heritage of the Eastern thinkers, their pedagogical views, especially the ideas of ethics, morality, piety, faith, conscience, diligence, humanity are the main tools for the comprehensive and harmonious development of the person. From this point of view, patriotism, freedom, humanism, hard work, evil - faith, honesty, moral purity, justice which the main figures in the educational and ethical views of the 14th-century mystic doctrine of Bahauddin Naqshband, one of the topical issues of the day is the inculcation of ideas of a harmonious human upbringing into the minds of students.